Positive pole piece, secondary battery and electronic device
By arranging a protective layer on the surface of the positive electrode material layer of the positive electrode sheet, the problem of side reactions caused by the crushing of HLM material particles is solved, and the high-temperature cycle performance of the secondary battery is improved.
Patent Information
- Application Number
- CN202411505124.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-24
AI Technical Summary
Lithium-rich manganese-based (HLM) materials increase the bare surface due to particle breakage in secondary batteries, which increases the possibility of side reaction with the electrolyte and affects the circulation performance. At the same time, the commonly used full covering method reduces the conductivity of the material and increases the impedance.
A positive electrode sheet is designed, which includes a positive electrode current collector and a positive electrode material layer provided on its surface. The surface of the positive electrode material layer is covered with a protective layer. The protective layer is connected to the cathode current collector and includes metal oxides, non-metal oxides, phosphates, fluorides or solid electrolytes. It is used to reduce side reactions between the cathode material layer and the electrolyte and improve the ions and electrons between HLM material particles. Conductive properties.
By reducing the side reactions of the positive material layer and electrolytes and improving ions and electronic conduction performance, the high temperature cycle performance of the secondary battery is significantly improved.
Smart Images

Figure CN119361597A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a positive electrode sheet, a secondary battery and an electronic device. Background Art
[0002] Lithium-rich manganese-based (HLM) materials have the advantages of low cost and high energy density, but the HLM material particles themselves have many pores. After cold pressing, the fine secondary particles are broken. As the cycle progresses, the HLM material particles become more and more broken. The broken material particles increase the exposed surface, and the possibility of side reactions with the electrolyte increases, which will affect the cycle performance of the secondary battery.
[0003] A common method is to coat the surface of HLM material particles with a protective layer to reduce the occurrence of side reactions with the electrolyte. However, this method of fully coating particles reduces the conductivity of HLM material particles and affects the impedance of secondary batteries, which urgently needs to be improved. Summary of the invention
[0004] The purpose of this application is to provide a positive electrode sheet, a secondary battery and an electronic device to improve the high temperature cycle performance of the secondary battery. The specific technical solution is as follows:
[0005] The first aspect of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein a protective layer is disposed on the surface of the positive electrode material layer, and the protective layer is connected to the surface of the positive electrode current collector. The positive electrode material layer comprises a positive electrode active material, and the positive electrode active material comprises a lithium-rich manganese-based material. The protective layer comprises at least one of a metal oxide, a non-metal oxide, a phosphate, a fluoride or a solid electrolyte, wherein the metal oxide comprises at least one of Al2O3, TiO2, ZnO, MgO, SnO2 or ZrO2, the non-metal oxide comprises at least one of SiO2, P2O5 or B2O3, the phosphate comprises at least one of Li3PO4, AlPO4 or FePO4, the fluoride comprises at least one of AlF3, MgF2, TiF4, WF6, NbF5, MoF4, MoF6 or ZrF4, and the solid electrolyte comprises Li7La3Zr2O 12 , Li 3y La 2 / 3-y TiO3 or Li 1.3 Al 0.3 Ti 1.7 At least one of (PO4)3, wherein 0.04≤y≤0.17. When the structure of the positive electrode sheet, the type of the positive electrode active material and the protective layer are within the scope of the present application, the possibility of side reactions between the positive electrode material layer and the electrolyte can be reduced, and the ion and electron conductivity between the HLM material particles can be improved, thereby improving the high temperature cycle performance of the secondary battery.
[0006] In one or more embodiments of the present application, the thickness of the protective layer is L nm, 0.2≤L≤20, preferably, 1≤L≤10. By regulating the thickness L of the protective layer within the scope of the present application, the protective layer has a suitable thickness, which can reduce the influence of the protective layer on the lithium ion diffusion effect, and better isolate the positive electrode material layer and the electrolyte, reduce the possibility of side reactions between the positive electrode material layer and the electrolyte, thereby improving the high temperature cycle performance of the secondary battery.
[0007] In one or more embodiments of the present application, the diffusion coefficient of the positive electrode sheet is D cm 2 / s,L 2 / D<2×10 19 The thickness of the protective layer will affect the diffusion of lithium ions in the positive electrode. 2 The value of / D is within the scope of the present application, the protective layer has a suitable thickness, and the positive electrode plate has a smaller lithium ion diffusion resistance, thereby further improving the high temperature cycle performance of the secondary battery.
[0008] In one or more embodiments of the present application, the diffusion coefficient of the positive electrode sheet is D cm 2 / s, 1×10 -18 ≤D≤1×10 -9 By adjusting the value of the diffusion coefficient D of the positive electrode sheet within the scope of the present application, the positive electrode sheet can have a smaller lithium ion diffusion resistance, thereby improving the high temperature cycle performance of the secondary battery.
[0009] In one or more embodiments of the present application, the elastic modulus of the protective layer is E GPa, and L×E<3000. By adjusting the value of L×E within the scope of the present application, the flexibility of the high elastic modulus protective layer can be increased, the thickness of the protective layer can be optimized, and the diffusion resistance of lithium ions can be reduced, thereby further improving the high temperature cycle performance of the secondary battery.
[0010] In one or more embodiments of the present application, the elastic modulus of the protective layer is E GPa, 1≤E≤300. By adjusting the value of the elastic modulus of the protective layer within the scope of the present application, the protective layer has good flexibility, can better adapt to the volume change of the positive electrode active material during the charge and discharge cycle, reduce the phenomenon of cracking and peeling, and enable the protective layer to better protect the positive electrode active material, thereby improving the high temperature cycle performance of the secondary battery.
[0011] In one or more embodiments of the present application, the chemical formula of the lithium-rich manganese-based material is xLi2MnO3·(1-x)LiMO2, wherein 0<x<1, and M includes at least one of Ni, Co or Mn. By regulating the chemical formula of the lithium-rich manganese-based material within the scope of the present application, the secondary battery can have a higher energy density and better high-temperature cycle performance.
[0012] In one or more embodiments of the present application, based on the mass of the positive electrode active material, the mass percentage of the lithium-rich manganese-based material is W1%, 1≤W1≤100. By regulating the mass percentage of the lithium-rich manganese-based material within the scope of the present application, the HLM material can have a suitable mass percentage, so that the secondary battery has a higher energy density and the high temperature cycle performance of the secondary battery is improved.
[0013] In one or more embodiments of the present application, the positive electrode active material further includes a first positive electrode material, and the first positive electrode material includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate (LiFePO4) or lithium manganese oxide. By regulating the type of the first positive electrode material within the scope of the present application, the high temperature cycle performance of the secondary battery can be improved.
[0014] The second aspect of the present application provides a secondary battery, which includes the positive electrode sheet in any of the above embodiments. Therefore, the secondary battery provided by the present application has good high-temperature cycle performance.
[0015] The third aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good high-temperature cycle performance.
[0016] Beneficial effects of the embodiments of the present application:
[0017] The present application provides a positive electrode plate, including a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein a protective layer is disposed on the surface of the positive electrode material layer, and the protective layer is connected to the surface of the positive electrode current collector. The positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes a lithium-rich manganese-based material. The protective layer includes at least one of a metal oxide, a non-metal oxide, a phosphate, a fluoride or a solid electrolyte, the metal oxide includes at least one of Al2O3, TiO2, ZnO, MgO, SnO2 or ZrO2, the non-metal oxide includes at least one of SiO2, P2O5 or B2O3, the phosphate includes at least one of Li3PO4, AlPO4 or FePO4, the fluoride includes at least one of AlF3, MgF2, TiF4, WF6, NbF5, MoF4, MoF6 or ZrF4, and the solid electrolyte includes Li7La3Zr2O 12 , Li3y La 2 / 3-y TiO3 or Li 1.3 Al 0.3 Ti 1.7 At least one of (PO4)3, wherein 0.04≤y≤0.17. When the structure of the positive electrode sheet, the type of the positive electrode active material and the protective layer are within the scope of the present application, the possibility of side reactions between the positive electrode material layer and the electrolyte can be reduced, and the ion and electron conductivity between the HLM material particles can be improved, thereby improving the high temperature cycle performance of the secondary battery.
[0018] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0020] Figure 1 It is a schematic diagram of the cross-sectional structure of a positive electrode sheet in the prior art;
[0021] Figure 2 It is a schematic diagram of the cross-sectional structure of a positive electrode plate in one embodiment of the present application.
[0022] Reference numerals: HLM material particles 11 ; protective layer 12 ; positive electrode current collector 13 ; positive electrode material layer 14 . DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0024] It should be noted that in the specific implementation of the present application, lithium-ion batteries are used as an example of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0025] Lithium-rich manganese-based (HLM) materials have the advantages of low cost and high energy density, but the HLM material particles themselves have many pores, and the fine secondary particles will break after cold pressing. As the secondary battery cycle progresses, the particle breakage becomes more and more serious, resulting in an increase in exposed surface, an increase in the possibility of contact with the electrolyte and side reactions, and a deterioration in the cycle performance of the secondary battery. A common method is to coat the surface of the HLM material particles with a protective layer, such as Figure 1 As shown, a protective layer 12 is coated on the surface of the HLM material particles 11 to form a physical barrier, which can reduce the occurrence of side reactions between the HLM material particles and the electrolyte. However, this method of fully coating the HLM material particles will reduce the conductivity between the HLM material particles, reduce the electrical conductivity of the material, and increase the impedance of the secondary battery.
[0026] The first aspect of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein a protective layer is disposed on the surface of the positive electrode material layer, and the protective layer is connected to the surface of the positive electrode current collector. The positive electrode material layer comprises a positive electrode active material, and the positive electrode active material comprises a lithium-rich manganese-based material. The protective layer comprises at least one of a metal oxide, a non-metal oxide, a phosphate, a fluoride or a solid electrolyte, wherein the metal oxide comprises at least one of Al2O3, TiO2, ZnO, MgO, SnO2 or ZrO2, the non-metal oxide comprises at least one of SiO2, P2O5 or B2O3, the phosphate comprises at least one of Li3PO4, AlPO4 or FePO4, the fluoride comprises at least one of AlF3, MgF2, TiF4, WF6, NbF5, MoF4, MoF6 or ZrF4, and the solid electrolyte comprises Li7La3Zr2O 12 , Li 3y La 2 / 3-y TiO3 or Li 1.3 Al 0.3 Ti 1.7 At least one of (PO4)3, wherein 0.04≤y≤0.17, illustratively, the value of y can be 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17 or a range consisting of any two of the above values. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode collector along its own thickness direction, or on two surfaces of the positive electrode collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the positive electrode collector, or it can be a partial area of the surface of the positive electrode collector. There is no special limitation in this application, as long as the purpose of this application can be achieved.
[0027] The inventors have found that the positive electrode active material in the positive electrode material layer includes HLM material particles. The commonly used method of fully coating the surface of HLM material particles will increase the electronic conduction impedance between the HLM material particles. Therefore, in order to reduce the electronic conduction impedance between the HLM material particles, a directional coating method can be used to deposit a protective layer on the surface and pores of the cold-pressed positive electrode sheet, thereby adding a protective layer on the contact interface between the electrolyte and the positive electrode material layer. Figure 2 As shown, in the positive electrode sheet after cold pressing, a protective layer 12 is provided on the surface of the positive electrode material layer 14, and the protective layer 12 is connected to the surface of the positive electrode collector 13. The protective layer can selectively isolate the interface between the electrolyte and the positive electrode material layer, which can reduce the possibility of side reactions; there is no protective layer between the HLM material particles, thereby reducing the ion and electron conduction resistance and improving the high temperature cycle performance of the secondary battery. The protective layer includes at least one of a metal oxide, a non-metallic oxide, a phosphate, a fluoride or a solid electrolyte. When the structure of the positive electrode sheet, the type of the positive electrode active material and the protective layer are within the scope of this application, the possibility of side reactions between the positive electrode material layer and the electrolyte can be reduced, and the ion and electron conduction performance between the HLM material particles can also be improved, thereby improving the high temperature cycle performance of the secondary battery.
[0028] In one or more embodiments of the present application, the thickness of the protective layer is L nm, 0.2≤L≤20, preferably, 1≤L≤10, and illustratively, the value of L can be 0.2, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or a range consisting of any two of the above values. By regulating the thickness L of the protective layer within the scope of the present application, the protective layer has a suitable thickness, which can reduce the influence of the protective layer on the lithium ion diffusion effect, and at the same time better isolate the positive electrode material layer and the electrolyte, reduce the possibility of side reactions between the positive electrode material layer and the electrolyte, thereby improving the high temperature cycle performance of the secondary battery.
[0029] In one or more embodiments of the present application, the diffusion coefficient of the positive electrode sheet is D cm 2 / s,L 2 / D<2×10 19 , for example, L 2 The value of / D can be 6.3×10 9 , 8.3×10 9 , 1.08×10 10 , 1.90×10 10 , 4.6×10 11 , 4.4×10 12 , 1.82×10 13 , 5.7×10 14 , 1.33×10 15, 6.9×10 16 , 1.72×10 18 Or it can be a range consisting of any two of the above values. The thickness of the protective layer will affect the diffusion of lithium ions in the positive electrode sheet. 2 The value of / D is within the scope of the present application, the protective layer has a suitable thickness, and the positive electrode plate has a smaller lithium ion diffusion resistance, thereby further improving the high temperature cycle performance of the secondary battery.
[0030] In one or more embodiments of the present application, the diffusion coefficient of the positive electrode sheet is D cm 2 / s, 1×10 -18 ≤D≤1×10 -9 , for example, the value of D can be 1×10 -18 , 1×10 -17 , 1×10 -16 , 1×10 -15 , 1×10 -14 , 1×10 -13 , 1×10 -12 , 1×10 -11 , 1×10 -10 , 1×10 -9 Or a range consisting of any two of the above values. By adjusting the value of the diffusion coefficient D of the positive electrode sheet within the scope of the present application, the positive electrode sheet can have a smaller lithium ion diffusion resistance, thereby improving the high temperature cycle performance of the secondary battery.
[0031] In one or more embodiments of the present application, the elastic modulus of the protective layer is E GPa, L×E<3000, and illustratively, the value of L×E can be 250, 500, 750, 1000, 1250, 1500, 1750, 2000, 2250, 2500, 2750, or a range consisting of any two of the above values. By adjusting the value of L×E within the scope of the present application, the flexibility of the high elastic modulus protective layer can be increased, the thickness of the protective layer can be optimized, and the diffusion resistance of lithium ions can be reduced, thereby further improving the high temperature cycle performance of the secondary battery.
[0032] In one or more embodiments of the present application, the elastic modulus of the protective layer is E GPa, 1≤E≤300. For example, the value of E can be 1, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, or a range consisting of any two of the above values. By regulating the value of the elastic modulus of the protective layer within the scope of the present application, the protective layer has good flexibility, can better adapt to the volume change of the positive electrode active material during the charge and discharge cycle, reduce the phenomenon of cracking and peeling, and enable the protective layer to better protect the positive electrode active material, thereby improving the high temperature cycle performance of the secondary battery.
[0033] In one or more embodiments of the present application, the chemical formula of the lithium-rich manganese-based material is xLi2MnO3·(1-x)LiMO2, wherein 0<x<1, illustratively, the value of x can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or a range consisting of any two of the above values; M includes at least one of Ni, Co or Mn. By regulating the chemical formula of the lithium-rich manganese-based material within the scope of the present application, the secondary battery can have a higher energy density, and the secondary battery has better high-temperature cycle performance.
[0034] In one or more embodiments of the present application, based on the mass of the positive electrode active material, the mass percentage of the lithium-rich manganese-based material is W1%, 1≤W1≤100, and illustratively, W1 can be 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 or a range consisting of any two of the above values. By regulating the mass percentage of the lithium-rich manganese-based material within the scope of the present application, the HLM material can have a suitable mass percentage, so that the secondary battery has a higher energy density and improves the high temperature cycle performance of the secondary battery.
[0035] In one or more embodiments of the present application, the positive electrode active material further includes a first positive electrode material, and the first positive electrode material includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate or lithium manganese oxide. In the present application, lithium nickel cobalt manganese oxide includes LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.5 Co0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.1 Mn 0.3 O2(NCM613) or LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 At least one of O2 (NCM111). By adjusting the type of the first positive electrode material within the scope of the present application, the high temperature cycle performance of the secondary battery can be improved. Based on the mass of the positive electrode active material, the mass percentage of the first positive electrode material is 0 to 99%.
[0036] The present application has no particular restrictions on the preparation method of the positive electrode sheet, and it can be any preparation method of the positive electrode sheet known to those skilled in the art. For example: after mixing the positive electrode active material, the conductive agent, and the binder, a solvent is added, and the positive electrode slurry is obtained after vacuum stirring, and the positive electrode slurry is evenly coated on one surface of the positive electrode collector, and after drying, a positive electrode sheet coated with a single-sided positive electrode material layer is obtained, and then the above steps are repeated on the other surface of the positive electrode collector to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. After the above-mentioned positive electrode sheet coated with a positive electrode material layer on both sides is cold-pressed, it is directionally coated by any method of magnetron sputtering, ion beam sputtering, pulsed laser deposition, atomic layer deposition or electron beam evaporation to obtain the desired positive electrode sheet. For example: after the positive electrode sheet coated with the positive electrode material layer on both sides is cold pressed, the atomic layer deposition technology (ALD) is used, O3 is used as an oxidant, Al(CH3)3 is used as a precursor, and a protective layer is set at the positive electrode sheet level in the temperature range of 100°C to 300°C, and a protective layer of a certain thickness is deposited on the positive electrode material layer and the surface of the positive electrode current collector to obtain the desired positive electrode sheet. The present application has no particular restrictions on the solvent, as long as the purpose of the present application can be achieved. For example, the solvent can be N-methylpyrrolidone (NMP).
[0037] The present application has no particular restrictions on the method of regulating the thickness L of the protective layer, as long as the purpose of the present application can be achieved. For example, the thickness L of the protective layer can be regulated by regulating the number of cycles of the atomic layer deposition technology. Generally, the more cycles of the atomic layer deposition technology are performed, the greater the value of the thickness L of the protective layer; the fewer cycles of the atomic layer deposition technology are performed, the smaller the value of the thickness L of the protective layer.
[0038] The present application has no particular restrictions on the method for regulating the diffusion coefficient D of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the diffusion coefficient D of the positive electrode sheet can be regulated by regulating the material type of the protective layer and / or the thickness of the protective layer. It should be noted that the diffusion coefficient of the positive electrode sheet in the present application is the diffusion coefficient of the lithium ions in the positive electrode sheet.
[0039] The present application has no particular limitation on the method for regulating the elastic modulus E of the protective layer, as long as the purpose of the present application can be achieved. For example, the elastic modulus E of the protective layer can be regulated by regulating the material type of the protective layer and / or the thickness of the protective layer.
[0040] The present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, aluminum foil, aluminum alloy foil or composite current collector (such as aluminum carbon composite current collector) can be included. The positive electrode material layer also includes a conductive agent and a binder. The present application does not particularly limit the types of conductive agents and binders, as long as the purpose of the present application can be achieved. For example, the binder may include polyacrylate, polyimide, polyamide, polyamide-imide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene-butadiene rubber), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, sodium hydroxymethyl cellulose or potassium hydroxymethyl cellulose. At least one of the conductive agent may include conductive carbon black, carbon nanotubes (CNTs), carbon fiber, flake graphite or graphene. Conductive carbon black may be at least one of acetylene black, Super P or Ketjen black. The present application does not particularly limit the mass ratio of the positive active material, conductive agent and binder in the positive electrode material layer. Those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved.
[0041] The present application has no particular limitation on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and the thickness of the single-sided positive electrode material layer is 30 μm to 120 μm.
[0042] The second aspect of the present application provides a secondary battery, which includes the positive electrode sheet in any of the above embodiments. Therefore, the secondary battery provided by the present application has good high-temperature cycle performance.
[0043] In the present application, the secondary battery also includes a negative electrode plate, and the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or it can be a partial area of the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0044] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.
[0045] The negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.
[0046] In some embodiments of the present application, the negative electrode material layer may further include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the above conductive agent and the above binder. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent, and the binder in the negative electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0047] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 30 μm to 120 μm.
[0048] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm.
[0049] Optionally, the negative electrode plate may further include a conductive layer, and the conductive layer is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, and it may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, and it may be at least one of the above conductive agent and the above binder.
[0050] In the present application, the secondary battery also includes a diaphragm. The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) films), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of diaphragm may include at least one of a woven membrane, a nonwoven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0051] In some embodiments of the present application, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0052] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0053] In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application is not particularly limited to inorganic particles, such as inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application is not particularly limited to binders, such as binders can be at least one of the above-mentioned binders. In some embodiments of the present application, the polymer layer includes polymers, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymers, polyacrylic acid, polyacrylates, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0054] In the present application, there is no particular limitation on the thickness of the separator as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 3 μm to 30 μm.
[0055] In the present application, the secondary battery further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.
[0056] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved.
[0057] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0058] The carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0059] The present application has no particular limitation on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the non-aqueous solvent is 85% to 92%.
[0060] The secondary battery of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.
[0061] The present application does not particularly limit the type of secondary battery, which may include any device that undergoes an electrochemical reaction. In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.
[0062] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and there is no particular limitation in the present application. For example, the preparation process of the secondary battery may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.
[0063] The third aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.
[0064] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0065] Example
[0066] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0067] Test methods and equipment:
[0068] Protective layer thickness L test:
[0069] The lithium-ion battery was disassembled after being discharged at a constant current of 0.1C to 2.5V. The positive electrode was then taken out and soaked in dimethyl oxalate (DMO) for 30 minutes to clean and remove the electrolyte and byproducts on the surface of the positive electrode. The positive electrode was then dried in a fume hood for 4 hours and the dried positive electrode was taken out. The morphology of the cross section of the positive electrode along the thickness direction was characterized by transmission electron microscopy (TEM), and the thickness of the protective layer was measured respectively. The test conditions of TEM were: in a high vacuum environment, the acceleration voltage was 200kV, the working mode was bright field (BF), and the sample stage was tilted 30°.
[0070] Lithium ion diffusion coefficient D test of positive electrode:
[0071] The lithium-ion battery was disassembled after being discharged to 2.5V at a constant current of 0.1C, and then the positive electrode was taken out, and the positive electrode was soaked in dimethyl oxalate (DMO) for 30 minutes, the electrolyte and by-products on the surface of the positive electrode were cleaned and removed, and then dried in a fume hood for 4 hours, and the dried positive electrode was taken out. The prepared positive electrode, negative electrode, diaphragm, and electrolyte were combined into a button cell, and the lithium ion diffusion coefficient was tested by electrochemical impedance spectroscopy (EIS). The preparation method of the above-mentioned negative electrode, diaphragm, and electrolyte is the same as that of Example 1-1. Specifically, an AC impedance test was performed on an electrochemical workstation with a frequency between 1mHz and 100kHz, and the impedance spectrum from 2.5V to 4.5V was measured, and the Nyquist diagram was drawn. The lithium ion diffusion coefficient was obtained by fitting the equivalent circuit model.
[0072] Elastic modulus E test of protective layer:
[0073] The lithium-ion battery was disassembled after being discharged to 2.5V at a constant current of 0.1C, and then the positive electrode was taken out and soaked in dimethyl oxalate (DMO) for 30 minutes to clean and remove the electrolyte and byproducts on the surface of the positive electrode, and then dried in a fume hood for 4 hours, and the dried positive electrode was taken out. The elastic modulus of the protective layer was tested by nanoindentation. By using a nanoindenter to apply force on the surface of the protective layer and record the depth of indentation, the mechanical response of the protective layer can be obtained, and the elastic modulus of the protective layer can be calculated according to the following formula:
[0074] Elastic modulus of protective layer E = S × A / π 1 / 2 , where S is the elastic contact stiffness, S = P / h, P is the surface force, h is the indentation depth, and A is the contact area of the nanoindenter.
[0075] Cycle performance test:
[0076] At 45°C, the lithium-ion battery is charged to 4.28V at a constant current of 0.5C, then charged to 0.025C at a constant voltage of 4.28V, left to stand for 5 minutes, and discharged to 3.0V at a constant current of 1C, left to stand for 5 minutes. The above is a charge and discharge cycle, and the discharge capacity of each cycle is recorded. The lithium-ion battery is cycled multiple times according to the above conditions, and the discharge capacity of the lithium-ion battery is measured after each cycle. With the capacity of the first discharge as 100%, the charge and discharge cycles are repeated until the discharge capacity retention rate decays to 80% of the first discharge capacity, the test is stopped, and the number of cycles is recorded as an indicator for evaluating the cycle performance of the lithium-ion battery. Discharge capacity retention rate (%) = (capacity after each discharge cycle / first discharge capacity) × 100%.
[0077] Example 1-1
[0078] <Preparation of positive electrode sheet>
[0079] The lithium-rich manganese-based material (0.5Li2MnO3·0.5LiMn 0.5 Ni 0.5 O2) and the first positive electrode material lithium manganate LiMn2O4 are mixed in a mass ratio of 1:9 to form a positive electrode active material. The above-mentioned positive electrode active material, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%, and the positive electrode slurry is obtained after vacuum stirring. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 15μm, and dried at 120°C to obtain a positive electrode sheet coated with a single-sided positive electrode material layer. Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides, and the coating weight of the positive electrode material layer is 180g / m 2 After coating, the positive electrode sheet was cold pressed, and the compaction density was 2.7g / cm 3 , and then using atomic layer deposition technology (ALD), with O3 as the oxidant and Al(CH3)3 as the precursor, a protective layer is set at the positive electrode plate level at a temperature of 200°C. The protective layer includes metal oxide Al2O3, that is, an Al2O3 protective layer with a thickness L of 2nm is deposited on the surface of the positive electrode material layer and the positive electrode current collector aluminum foil, and then cut into pieces and welded to the pole ears to obtain a positive electrode plate with a specification of 74mm×867mm for standby use.
[0080] <Preparation of negative electrode sheet>
[0081] The negative electrode active material artificial graphite, the conductive agent Super P, and the binder polyacrylic acid are mixed in a weight ratio of 97.3:1.5:1.2, and deionized water (H2O) is added as a solvent to prepare a slurry with a solid content of 70wt%, and stirred evenly to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, and dried at 110°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. The coating weight of the negative electrode material layer is 95g / m 2 After coating, the negative electrode sheet is cold pressed, and the compaction density is 1.7g / cm 3 After cutting and welding the tabs, the negative electrode sheet with a specification of 78mm×875mm is obtained for standby use.
[0082] <Preparation of Electrolyte>
[0083] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were mixed uniformly at a mass ratio of EC:EMC:DEC=3:5:2 to obtain a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) was added to the base solvent and mixed uniformly to obtain an electrolyte. The mass percentage of the lithium salt was 12.5% based on the mass of the electrolyte, and the remainder was the base solvent.
[0084] <Diaphragm>
[0085] A polyethylene film with a thickness of 9 μm was selected as the separator.
[0086] <Preparation of lithium-ion batteries>
[0087] The positive electrode sheet, separator, negative electrode sheet and separator are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an aluminum-plastic film, and then the prepared electrolyte is injected, and a lithium-ion battery is obtained after the steps of formation, degassing and trimming.
[0088] Example 1-2 to Example 1-18
[0089] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0090] Example 2-1 to Example 2-2
[0091] Except for adjusting the mass percentage W1 of the lithium-rich manganese-based material according to Table 2, the rest is the same as Example 1-1. The sum of the mass percentage W1 of the lithium-rich manganese-based material and the mass percentage W2 of the first positive electrode material is 100%.
[0092] Example 2-3 to Example 2-4
[0093] Except for adjusting the type of the first positive electrode material according to Table 2, the rest is the same as Example 1-1.
[0094] Comparative Example 1
[0095] Except for preparing the positive electrode sheet according to the following method, the rest is the same as Example 1-1.
[0096] <Preparation of positive electrode sheet>
[0097] The lithium-rich manganese-based material (0.5Li2MnO3·0.5LiMn 0.5 Ni 0.5O2) and lithium manganate LiMn2O4 are mixed in a mass ratio of 1:9 to prepare a positive electrode active material. The above-mentioned positive electrode active material, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%, and the positive electrode slurry is obtained after vacuum stirring. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 15μm, and dried at 120°C to obtain a positive electrode sheet coated with a single-sided positive electrode material layer. Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. After drying at 120°C, cold pressing is performed, and then cutting and welding of the pole ears are performed to obtain a positive electrode sheet with a specification of 74mm×867mm for standby use. Among them, the coating weight of the positive electrode material layer is 180g / m 2 The compaction density of the cold pressing process is 2.7g / cm 3 .
[0098] The preparation parameters and electrical performance parameters of each embodiment and comparative example are shown in Table 1 and Table 2.
[0099] Table 1
[0100]
[0101]
[0102] Note: “ / ” in Table 1 indicates that there is no corresponding preparation parameter or substance.
[0103] It can be seen from Examples 1-1 to 1-18 and Comparative Example 1 that by adjusting the structure of the positive electrode sheet, the type of positive electrode active material and the type of protective layer material within the scope of this application, the lithium-ion battery has a higher number of cycles, indicating that the high-temperature cycle performance of the lithium-ion battery is good. In Comparative Example 1, no protective layer is provided on the surface of the positive electrode material layer, and the number of cycles of the lithium-ion battery is low, indicating that the high-temperature cycle performance of the lithium-ion battery is poor.
[0104] It can be seen from Examples 1-1, 1-13 to 1-18 that by adjusting the thickness L of the protective layer within the scope of this application, the number of cycles of the lithium-ion battery is improved, which shows that the high-temperature cycle performance of the lithium-ion battery is improved. It can be seen from Examples 1-1, 1-13 to 1-18 that with the increase of the thickness L of the protective layer, the number of cycles of the lithium-ion battery shows a trend of first increasing and then decreasing, which shows that the lithium-ion battery with a thickness L of the protective layer in the range of 1≤L≤10 has better high-temperature cycle performance.
[0105] It can be seen from Examples 1-1 to 1-12 that by regulating the diffusion coefficient D of the positive electrode sheet within the scope of the present application, the number of cycles of the lithium-ion battery is improved, which indicates that the high-temperature cycle performance of the lithium-ion battery is improved.
[0106] It can be seen from Examples 1-1 to 1-18 that by regulating L 2 / D Within the scope of this application, the number of cycles of the lithium-ion battery is improved, which indicates that the high-temperature cycle performance of the lithium-ion battery is improved.
[0107] It can be seen from Examples 1-1 to 1-12 that by adjusting the elastic modulus E of the protective layer within the scope of the present application, the number of cycles of the lithium-ion battery is improved, which indicates that the high-temperature cycle performance of the lithium-ion battery is improved.
[0108] It can be seen from Examples 1-1 to 1-18 that by regulating the product L×E of the elastic modulus E of the protective layer and the thickness L of the protective layer within the scope of this application, the number of cycles of the lithium-ion battery is improved, indicating that the high-temperature cycle performance of the lithium-ion battery is improved.
[0109] Table 2
[0110]
[0111] Note: “ / ” in Table 2 indicates that there is no corresponding preparation parameter or substance.
[0112] It can be seen from Example 1-1, Example 2-1 to Example 2-2 that by adjusting the mass percentage content W1 of the lithium-rich manganese-based material within the scope of this application, the number of cycles of the lithium-ion battery is improved, indicating that the high temperature cycle performance of the lithium-ion battery is improved.
[0113] It can be seen from Example 1-1, Example 2-3 to Example 2-4 that by adjusting the type of the first positive electrode material within the scope of the present application, the number of cycles of the lithium-ion battery is improved, which indicates that the high-temperature cycle performance of the lithium-ion battery is improved.
[0114] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0115] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0116] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein a protective layer is disposed on the surface of the positive electrode material layer, and the protective layer is connected to the surface of the positive electrode current collector; The positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes a lithium-rich manganese-based material; The protective layer includes at least one of a metal oxide, a non-metal oxide, a phosphate, a fluoride or a solid electrolyte, the metal oxide includes at least one of Al2O3, TiO2, ZnO, MgO, SnO2 or ZrO2, the non-metal oxide includes at least one of SiO2, P2O5 or B2O3, the phosphate includes at least one of Li3PO4, AlPO4 or FePO4, the fluoride includes at least one of AlF3, MgF2, TiF4, WF6, NbF5, MoF4, MoF6 or ZrF4, the solid electrolyte includes Li7La3Zr2O 12 , Li 3y La 2 / 3-y TiO3 or Li 1.3 Al 0.3 Ti 1.7 At least one of (PO4)3, wherein 0.04≤y≤0.17。 2. The positive electrode sheet according to claim 1, wherein: The thickness of the protective layer is L nm, 0.2≤L≤20.
3. The positive electrode sheet according to claim 2, wherein: 1≤L≤10。 4. The positive electrode sheet according to claim 2 or 3, wherein: The diffusion coefficient of the positive electrode is D cm 2 / s,L 2 / D<2×10 19 .
5. The positive electrode sheet according to claim 4, wherein: 1×10 -18 ≤D≤1×10 -9 。 6. The positive electrode sheet according to claim 2 or 3, wherein: The elastic modulus of the protective layer is E GPa, L×E<3000.
7. The positive electrode sheet according to claim 6, wherein: 1≤E≤300。 8. The positive electrode sheet according to claim 1, wherein: The chemical formula of the lithium-rich manganese-based material is xLi2MnO3·(1-x)LiMO2, wherein 0<x<1, and M includes at least one of Ni, Co or Mn.
9. The positive electrode sheet according to claim 1, wherein: Based on the mass of the positive electrode active material, the mass percentage of the lithium-rich manganese-based material is W1%, 1≤W1≤100.
10. The positive electrode sheet according to claim 1, wherein: The positive electrode active material further includes a first positive electrode material, and the first positive electrode material includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate or lithium manganese oxide. 11 . A secondary battery, comprising the positive electrode sheet according to claim 1 . 12 . An electronic device comprising the secondary battery according to claim 11 .
Citation Information
Cited By
Positive pole piece, preparation method thereof and battery
CN120690807A
Lithium manganate positive electrode material and preparation method and application thereof
CN121601631A
Lithium manganate positive electrode material and preparation method and application thereof
CN121601631B